LEVEL OF DISCIPLINE ADHERING TO HEALTH PROTOCOLS AND VACCINATION WILLINGNESS AS PART OF COVID 19 CONTROL EFFORTS IN INDONESIA - Naris Dyah Prasetyawati; Sigid Sudaryanto; Desi Fupix Usmaningrum (Bajang Institute, 2022)
The COVID-19 pandemic, which has been set since March 2020 until now, has impacted various aspects of human life. Restricting community activities is the primary key to breaking the chain of transmission of Covid 19. Changes in human behavior patterns have also changed following current conditions towards adapting to new habits. This study aims to describe the level of community discipline in implementing health protocols and the public's willingness to vaccinate. The sampling method was taken randomly using a form opened within two weeks with the number of respondents filling out 241 respondents. The conclusion in this study was that the level of discipline of the respondents in applying the use of masks, washing hands using soap and air showed promising results and supported the discipline of implementing health protocols. The point that still needs attention is that measures to maintain distance, avoid use and reduce activities are still in the category that is lacking in implementation. While public perception of vaccines and availability for vaccines is also good, there are still a small number of people who doubt the vaccines and the methods used.